2018
DOI: 10.30540/sae-2018-001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Support Closed Section Ribs on the Critical Moment for Lateral Torsional Buckling of Steel Beams

Abstract: The study presents the results of theoretical investigations into the effect produced by support closed section ribs on the critical moment for lateral torsional buckling (Mcr) of bisymmetric I-beams. Elastic restraint against warping, at the site of support, was provided by closed section ribs made from selected rolled profiles (longitudinally cut circular tubes, angles, and channels). Detailed calculations were made for beams under uniform load applied to the top flange of the section. The results obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It was shown that the use of support ribs with closed section significantly increased the critical loading of the beams of under consideration. In study [37], the influence of various types of supporting ribs with a closed cross-section on the critical moment of the lateral torsional buckling for differently loaded beams was examined. Detailed calculations were made for uniformly loaded beams.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the use of support ribs with closed section significantly increased the critical loading of the beams of under consideration. In study [37], the influence of various types of supporting ribs with a closed cross-section on the critical moment of the lateral torsional buckling for differently loaded beams was examined. Detailed calculations were made for uniformly loaded beams.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the warping stiffness of different types of stiffeners [ 31 , 32 ] showed that the effect produced by curbing the beam section’s warping was negligibly small when flat stiffeners (of commonly found thicknesses) were used, compared with closed-section stiffeners. Consequently, the contribution of flat stiffeners t p = 8 mm, located in the axis of the B–E critical beam ( Figure 1 b), was neglected when the stiffness of the beam elastic restraint against warping α ω (6) was determined, i.e., it was assumed that α ω R = 0.…”
Section: The Model Of Designated Critical Beam (Methods 3)mentioning
confidence: 99%
“…For each of the span variants, two types of stiffening were taken into consideration at joints B and E, namely flat stiffeners ( Figure 1 b) and closed-section stiffeners ( Figure 1 c). These two methods of stiffening are characterised by a large disparity in the obtained warping stiffness [ 31 , 32 ]. It was assumed that the homogeneous grillage beams were weld-connected at joints B and E. In this way, it was possible to obtain full continuity in the transmission of displacements, including warping, and in the transmission of cross-sectional forces, including bimoments.…”
Section: Diagram Of the Analysed Structurementioning
confidence: 99%
“…In order to enhance beam resistance to LTB, systems of support ribs for beams (spandrel beams) were developed. They were meant to increase the deplanation rigidity of support cross sections [33][34][35][36][37][38]. Methods for analysing beams discretely braced along their span were discussed in [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that ribs (especially closed ones) and discrete elastic bracings considerably affect the values of critical loads. The authors of [20,23,33,34,36,37,[43][44][45][46], analysed the impact of elastic restraint against warping of support cross sections for single-span beams with bisymmetric cross sections. The impact of elastic restraint against warping of the cantilever beam free end on its critical resistance caused by the LTB condition was examined in [47].…”
Section: Introductionmentioning
confidence: 99%